Pengembangan Desain Didaktis Pada Pembelajaran Geometri - Hidayat Hidayat; Siti Khayroiyah (Jurnal MathEducation Nusantara, 2018)
Abstract Problems that occur in learning circle one of them is the low ability of students in understanding the concept. Understanding broad concepts of circles can be helped by using teaching materials as learning media. The teaching material should be a didactic design that is designed with due regard to the concepts, principles, object of study, and characteristics of the students. The formulation of the problem in this research is how didactic design development to improve the ability to solve the problem of student circle in accordance with obstacle learning? Specific objectives to be achieved are wide circular didactic design and increasing ability to solve circle problems. This research is a research of didactic design development with 3-D model by Thiagarajan done through Define, Design, and Develop stage Keywords: Didaktis Design, Circle Learning